Regression of Castration-Resistant Prostate Cancer by a Novel Compound HG122 - Cong, Xiaonan; He, Yundong; Wu, Haigang; Wang, Dingxiang; Liu, Yongrui; Shao, Ting; Liu, Mingyao; Yi, Zhengfang; Zheng, Jianghua; Peng, Shihong; Ding, Tao (Frontiers in Oncology, 2021)
Prostate cancer (PCa) is a common aggressive disease worldwide which usually progresses into incurable castration-resistant prostate cancer (CRPC) in most cases after 18–24 months treatment. Androgen receptor (AR) has been considered as a crucial factor involved in CRPC and the study of AR as a potential therapeutic target in CRPC may be helpful in disease control and life-cycle management. In this study, we identified a potent small molecule compound, HG122, that suppressed CRPC cells proliferation and metastasis, and inhibited tumor growth both in subcutaneous and orthotopic tumor model. In addition, HG122 reduced the mRNA expression of PSA and TMPRSS2 which are target genes of AR, resulting in cell growth inhibition and metastasis suppression of CRPC, without affecting the expression of AR mRNA level. Mechanically, HG122 promoted AR protein degradation through the proteasome pathway impairing the AR signaling pathway. In conclusion, HG122 overcomes enzalutamide (ENZ) resistance in CRPC both in vitro and in vivo, thus suggesting HG122 is a potential candidate for the clinical prevention and treatment of CRPC.